The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jare.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Volatile aroma components and MS-based electronic nose profiles of dogfruit ( Pithecellobium jiringa ) and stink bean ( Parkia speciosa )

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Phenolic compounds and flavonoids were detected by spectrophotometric method using gallic acid as standard and aluminum chloride or catechin standard [18]. Further isolation and quantification of phenolic, flavonoid compounds, and other volatile compounds were detected by thin layer chromatography (TLC), high-performance liquid chromatography (HPLC), UPLC, and mass spectroscopy (MS) loaded with high specified columns [20]. Gallic acid, rutin, vanillic acid were detected by CP-Sil 8 capillary column and catechin, epicatechin were detected by DB-5 capillary column [21].…”
Section: Extraction Of Bioactive Compoundsmentioning
confidence: 99%
See 3 more Smart Citations
“…Phenolic compounds and flavonoids were detected by spectrophotometric method using gallic acid as standard and aluminum chloride or catechin standard [18]. Further isolation and quantification of phenolic, flavonoid compounds, and other volatile compounds were detected by thin layer chromatography (TLC), high-performance liquid chromatography (HPLC), UPLC, and mass spectroscopy (MS) loaded with high specified columns [20]. Gallic acid, rutin, vanillic acid were detected by CP-Sil 8 capillary column and catechin, epicatechin were detected by DB-5 capillary column [21].…”
Section: Extraction Of Bioactive Compoundsmentioning
confidence: 99%
“…Organosulfide compounds are source of polysulfides and active donor of hydrogen sulfide, and are responsible for peculiar flavor of P. speciosa. Skeleton of polysulfide in P. speciosa contained five to eight-membered carbon ring with three to six sulfur atoms in S-C-S arrangements [20]. The active hydrogen sulfides assist in cardioprotective vascular cell signaling molecules that are associated with various cardiovascular health benefits and reduction of systolic blood pressure [20,34].…”
Section: Organosulfide Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a current study, thirteen sulphurous compounds were identified in unripe, mid-ripe and ripe PS, where during ripening these compounds increased from 7.1 to 20.13%. Major components are 1,2,4-trithiolane, methanethiol and hydrogen sulfide [83]. Djenkolic acid identified in PS is formed from the dithiocetal (S-C-S), might be formed from formaldehyde and two molecules of cycteine [81].…”
Section: Saponinsmentioning
confidence: 99%